Exploring marine-derived bacterial compounds targeting the μ-opioid receptor agonists through metabolic profiling to molecular modeling - Daouia Boudrahem; Omar Messaoudi; Sarah Balit; Mouloud Kecha; Joachim Wink; Chirag N. Patel (Scientific Reports)
Abstract Given the severe side effects of prolonged morphine use, the search for safer alternatives is a global priority. This study investigates marine bacteria from sediments along the Bejaia coast, Algeria, to identify opioid-like bioactive compounds with potential analgesic properties. A total of 45 bacterial strains were isolated using six different culture media, with 18 strains exhibiting antimicrobial activity. Molecular identification based on 16S rRNA gene sequencing classified these strains into six genera: Streptomyces, Nocardiopsis, Alloalcanivorax, Pseudonocardia, Sinomicrobium, and Lysinibacillus. One strain, S5T2H1, was identified as a new Streptomyces species through a polyphasic approach. LC-HRESIMS analysis of secondary metabolites revealed that strain S56T3J31 produced A58365A, antimycin A, and three potentially novel compounds. However, strain S5T2H1 synthesized cyclo(phenylalanyl-prolyl) and niphimycin Ia, along with three unidentified metabolites, while strain S7T2H1 secreted a single compound identified as berberifuranol. Molecular docking and molecular dynamics simulations demonstrated that A58365A exhibited strong interactions with the μ-opioid receptor (5C1M), showing a stable binding affinity comparable to morphine. These findings highlight marine-derived bacterial compounds as promising candidates for opioid drug development.